Framing Analysis of News about Putri Ariani Winning the Golden Buzzer at America's Got Talent 2023 in Online Media Liputan6.com and Kompas.com - Tawvicky Hidayat; Ulfa Utami (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This research uses a qualitative descriptive method. Through a media text analysis approach with a focus on the issue of reporting on Putri Ariani. This type of qualitative research means that the researcher describes physical conditions and social conditions based on actual facts and data. Robert N Entman's analysis has four dimensions in the analysis, namely, Defining Problems, Diagnosing Causes, Moral Judgment/Evaluation, Treatment Recommendation. Where each news item will be analyzed one by one to find out the pattern of news construction created by the two media. Through media text analysis of Robert N Entman's framing model, the researcher draws conclusions regarding the formulation of the research problem. The author concludes that the frame built by Liputan6.com looks at the news. that Putri Ariani became the public spotlight after her stunning performance at America's Got Talent 2023. Meanwhile, the frame built by Kompas.com saw the news about Putri Ariani as a fact that could be seen in foreign media.